2016
DOI: 10.1051/shsconf/20163000020
|View full text |Cite
|
Sign up to set email alerts
|

Role of the family, friends and significant others in providing social support and enhancing quality of life in cancer patients

Abstract: Abstract.Cancer is a disease that may potentially affect woman's daily life, including her physical activities, career and social life. Women dealing with cancer can benefit from supportive relationships, and there was found evidence of moderating effect of social support on the harmful effect of stressful events, including life-threatening disease and patient's quality of life. The aim of this study was to examine the impact of socio-demographic factors (age, education, employment and marital status, number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
7
1
Order By: Relevance
“…The perception of close supportive relationships, including those of spouse and family members, is positively correlated with coping and adjustment by women diagnosed with breast cancer . Another study concluded that social support affects not only adjustment but also the survival of patients . An Indian study stated that the scores of H/H in response to mental adjustment decrease with an increase in social support for cancer patients .…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…The perception of close supportive relationships, including those of spouse and family members, is positively correlated with coping and adjustment by women diagnosed with breast cancer . Another study concluded that social support affects not only adjustment but also the survival of patients . An Indian study stated that the scores of H/H in response to mental adjustment decrease with an increase in social support for cancer patients .…”
Section: Introductionsupporting
confidence: 87%
“…18 Another study concluded that social support affects not only adjustment but also the survival of patients. 19 An Indian study stated that the scores of H/H in response to mental adjustment decrease with an increase in social support for cancer patients. 20 Another study observed a correlation between social support, especially emotional support from family members, and psychological adjustment with cancer.…”
mentioning
confidence: 99%
“…According to (Moore et al, 2016) the results of research conducted by patients who have undergone chemotherapy cannot meet the needs of children such as before undergoing chemotherapy, this is due to a decrease in the physical and psychological conditions experienced by patients, this change is an activity in managing the household (Banoycinova & Baskova, 2014). The impact of these changes creates psychological distress for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Acording to Shosha and Kalaldeh (2017) after one year since diagnosis of disease, perceived social support tends to decrease. The immediate family and people provide supports at the beggining of the diagnosis but from time to time the perceived support begins to decrease (Banovcinova & Baskova, 2014). The longer suffering from the disease makes a person resigned to treatment different from the time span of the sick who still have high expectations of treatment (Satari et al, 2012).…”
Section: Discussionmentioning
confidence: 99%